Role of Rescue 1122 in Wildlife Welfare in Punjab, Pakistan - Muhammad Sajid Rana; Fakhar -i-Abbas; Fakhra Nazir; Kainaat William (Journal of Bioresource Management, 2020)
Rescue 1122 emergency services in Punjab (Pakistan) also responds to calls when residents feel threatened from wild animals. Emergency calls received between August 2015 and July 2016 recorded 16 arthropod, 25 mammal, 156 bird, 816 reptile and 264 un-identified cases from different parts of the Punjab, which were safely handled and in majority of cases animals were safely released back in nature.